2011
DOI: 10.1017/s0147547911000159
|View full text |Cite
|
Sign up to set email alerts
|

From Geneva to the Americas: The International Labor Organization and Inter-American Social Security Standards, 1936–1948

Abstract: Beginning in the mid-1930s, Western Hemisphere nations turned to social insurance legislation--guided by the new concept of social security--in response to the economic crisis of the Great Depression. Supported by the International Labor Organization (ILO), national-level policy makers introduced a range of measures in recognition of the 1935 US Social Security Act. As Europe descended into a war, inter-Americanism served as way to maintain regional economic, and later military, security. This article describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
0
4
0
4
Order By: Relevance
“…Packard (2016), among others, has suggested that the Geneva institutions championed social medicine's programme of broader, systemic social and economic reforms, in sharp contrast with the outlook of the PASB and the IHD, which tended to support laboratory research and narrow, technical public health interventions, especially against infectious and vector-borne disease. Yet during the 1930s and 1940s the US supported the expansion of welfare states in Latin America, by promoting its own model of social security developed during Roosevelt's New Deal (Cohen, 1942;Jensen, 2011;Singleton, 2012). No doubt, the US exercised outsized influence in the PASB, but at the regular Pan-American Sanitary Conferences, US representatives exercised only loose control over the meeting agendas, and these meetings became a forum for discussion of a wide range of policy approaches, including some inspired in social medicine.…”
Section: Institutional Panoramamentioning
confidence: 99%
See 2 more Smart Citations
“…Packard (2016), among others, has suggested that the Geneva institutions championed social medicine's programme of broader, systemic social and economic reforms, in sharp contrast with the outlook of the PASB and the IHD, which tended to support laboratory research and narrow, technical public health interventions, especially against infectious and vector-borne disease. Yet during the 1930s and 1940s the US supported the expansion of welfare states in Latin America, by promoting its own model of social security developed during Roosevelt's New Deal (Cohen, 1942;Jensen, 2011;Singleton, 2012). No doubt, the US exercised outsized influence in the PASB, but at the regular Pan-American Sanitary Conferences, US representatives exercised only loose control over the meeting agendas, and these meetings became a forum for discussion of a wide range of policy approaches, including some inspired in social medicine.…”
Section: Institutional Panoramamentioning
confidence: 99%
“…In the following decade, the ILO continued to strengthen its ties to Latin American states, by holding two more regional conferences in Havana in 1939 and Mexico in 1946, establishing several branch offices in the region, and working to develop a cadre of technical experts in social security (Jensen, 2011;Plata-Stenger, 2015). Meanwhile, social security was integrated into the hemispheric public health agenda: the Tenth Pan-American Sanitary Conference in Bogotá in 1938, sponsored by the PASB, offered express support for social security as a 'means to defend collective health' (Oficina Sanitaria Panamericana, 1938, p. 4).…”
Section: Social Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…En los últimos años se han multiplicado las indagaciones sobre el accionar de la OIT en la configuración global y regional de las relaciones laborales (CARUSO et al, 2018;STAGNARO, 2017;FERRERAS, 2019;JENSEN, 2011;MAUL, 2019;RODGERS et al, 2009;YÁÑEZ ANDRADE, 2016). Este incremento de las investigaciones es tributario tanto del denominado "giro transnacional" de la historia social del trabajo (ECKERT, 2015) como de las iniciativas de producción de conocimiento impulsadas por la propia OIT en ocasión de su reciente centenario (BORIS et al, 2018;GAUDIER, 1996;KOTT, 2013;MAUL, 2019).…”
unclassified
“…El trabajo en las distintas sesiones temáticas convocó a expertos, funcionarios gubernamentales y representantes obreros en una coyuntura clave para la ordenación de las relaciones laborales continentales. A los desafíos planteados por el creciente proceso de ordenación del trabajo asalariado, y los debates en curso sobre los alcances de los seguros sociales (JENSEN, 2011;FLIER, 2006) se sumaba la necesidad de atender las consecuencias sociales y políticas de la crisis económica de 1930, especialmente la desocupación y las migraciones. El ascenso del fascismo, el crecimiento del activismo obrero y radicalización de los conflictos laborales, los avances del comunismo y, más adelante, la expansión bélica del nazismo en Europa presentaba un horizonte incierto para el desarrollo de las relaciones económicas mundiales (FERRERAS, 2012, p. 9;ANSALDI, 2003).…”
unclassified